Bargaining Power and Local Heroes - Ulrich Heimeshoff; Gordon Klein (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Retailer bargaining power is an important aspect of many international antitrust investigations. Size and market share analysis are often the cornerstones of bargaining power identi cation. However, other factors, like consumer behavior, i.e. "one-stop shopping", can heavily a ect the bargaining environment. We show and quantify, analyzing a natural experiment of a supply boycott of small local beer breweries towards a national retailer, that "one-stop shopping" leads to severe purchasing externalities, which is a novel nding. This results in a shift in the bargaining position in favor of the manufacturer, which is elevant for antitrust investigations. Neglecting those externalities in investigations and focusing mainly on size arguments may lead to a wrong assessment of bargaining power. Therefore a careful a case by case analysis of bargaining power is necessary in antitrust investigations.
Keywords: L42; L81; L13; 330